High tibial osteotomy effectively redistributes compressive knee loads during walking. Issue 3 (6th July 2022) - De Pieri, Enrico; Nüesch, Corina; Pagenstert, Geert; Viehweger, Elke; Egloff, Christian; Mündermann, Annegret
Abstract: The objectives of this study were to estimate pre‐ and postoperative lower limb kinematics and kinetics and knee intra‐articular forces during gait using musculoskeletal modeling in a cohort of patients with knee osteoarthritis (OA) undergoing high tibial osteotomy (HTO), compare these to controls, and determine correlations between changes in these parameters and Knee Injury and Osteoarthritis Outcome Score (KOOS) subscores after HTO. Sixteen patients with isolated, symptomatic medial compartment knee OA completed pre‐ and postoperative gait analysis (mean follow‐up time: 8.6 months). Sixteen age‐ and sex‐matched asymptomatic volunteers participated as controls. Musculoskeletal modeling was used to evaluate lower limb joint moments and knee contact forces during gait. While HTO had limited influence on sagittal plane kinematics and moments, significant changes in the load distribution at the knee after HTO were observed with a lower postoperative compressive load on the medial compartment during midstance and a higher compressive load on the lateral compartment during early and late stance. Moreover, the lateral shear force in midstance was significantly lower after HTO. Changes in the external knee adduction moment (KAM) did not always coincide with reductions in the knee compressive force in the medial compartment. Biomechanical changes did not correlate with improvements in KOOS subscores. Hence, HTO effectively unloaded the medial compartment by redistributing part of the overall compressive force to the lateral compartment during gait with limited influence on gait function. The KAM may not adequately describe compartmental load magnitude or changes induced by interventions at the compartment level. Clinical trial registration: ClinicalTrials. gov Identifier—NCT02622204. Clinical significance: This study provides important evidence for changes in joint level loads after corrective osteotomy as joint preserving surgery and emphasizes the need for additional biomechanical outcomes of such interventions.